Alpha-gal syndrome and the gastrointestinal reaction: a narrative review - Propst, Susan B. H.; Thompson, Dorothea K. (Frontiers in Allergy, 2025)
Gastrointestinal (GI) disturbances such as abdominal pain, nausea, and diarrhea are infrequently attributed to food allergies as an initial diagnosis in the absence of more traditional allergic reactions like hives, angioedema, or anaphylaxis. Alpha-gal syndrome (AGS) is an atypical and under-recognized allergy characterized by a delayed hypersensitivity reaction to the oligosaccharide galactose-α-1,3-galactose, a carbohydrate found in non-primate mammalian meat and derived products. This review of the current literature on AGS focuses on GI manifestations and diagnostic challenges. While clinical presentations of AGS vary widely, predominant or isolated GI symptoms, when manifested, can overlap with other disorders, thus making a timely and accurate diagnosis challenging. Here we provide an updated review of the epidemiology, pathophysiology, clinical presentation, and management of AGS. Current diagnostic approaches, treatment strategies, and areas requiring further research are also discussed.